Pengaruh Faktor Budaya dan faktor Sosial terhadap Keputusan Pembelian Hand and Body Lotion Scarlett pada Aplikasi Shopee - Maulida Naba Samawati; Abdul Yusuf (Economic Reviews Journal, 2024)
This research aims to determine the influence of cultural factors and social factors on purchasing decisions for Scarlett hand and body lotion on the Shopee application. The sample determination technique uses the rule of thumb with a sample size of 100 respondents from West Java. The method used in this research is a quantitative method with SEM-PLS analysis and assisted by the SMART-PLS analysis tool. The results of this research prove that cultural factors have a significant influence on purchasing decisions. However, social factors do not significantly influence purchasing decisions.